Seawater pearl hydrolysate alleviates perimenopausal syndrome by modulating hypothalamic and uterine ERα/MAPK/CREB signaling in ovariectomized rats - Deng, Yasheng; Liang, Tianwei; Huang, Hui; Han, Siyin; Fan, Yanping; Lin, Jiang (Frontiers in Pharmacology, 2026)
BackgroundPerimenopausal syndrome (PMS), characterised by hormonal imbalance resulting from ovarian aging, causes various symptoms that significantly impair quality of life. Current hormone replacement therapy carries potential risks; thus, safer alternatives are needed. This study investigated the therapeutic efficacy and underlying mechanisms of seawater pearl hydrolysate (SPH) against PMS in an ovariectomized (OVX) rat model, focusing on the estrogen receptorα (Erα)/mitogen-activated protein kinase (MAPK)/cAMP-responsive element-binding protein (CREB) signaling pathway.MethodsA PMS rat model was established via bilateral ovariectomy. Rats were divided into Sham, Model, Kuntai capsule (KT, positive control), and low-, medium-, and high-dose SPH groups. After 15 days of treatment, we assessed estrous cycles, open-field behavior, serum sex hormones [estradiol (E2), progesterone (P), follicle-stimulating hormone (FSH), luteinizing hormone (LH), gonadotropin-releasing hormone (GnRH), testosterone (T), anti-Müllerian hormone (AMH), oxidative stress markers (malondialdehyde (MDA), superoxide dismutase (SOD)], lipid profiles [total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C)], uterine histopathology, and mRNA/protein expression of key components [ERα, mitogen-activated protein kinase kinase 1 (MAP2K1), extracellular signal-regulated kinase (ERK), CREB] in uterine and hypothalamic tissues.ResultsCompared with the sham group, model rats showed disrupted estrous cycles, decreased locomotor activity, reduced uterine and hypothalamic indices, abnormal tissue morphology, significantly reduced serum levels of E2 and P, and elevated levels of FSH, LH, and GnRH. SPH treatment, particularly at medium and high doses, reversed OVX-induced impairments in a dose-dependent manner. Specifically, SPH ameliorated behavioural deficits, restored estrous cycles, improved uterine histoarchitecture, and normalised serum hormone levels (E2, P, FSH, LH). Additionally, SPH reduced oxidative stress (MDA) and improved dyslipidaemia. Mechanistically, these therapeutic effects were associated with increased mRNA and protein expression (including phosphorylation) of ERα, MAP2K1, ERK, and CREB in uterine and hypothalamic tissues.ConclusionSPH effectively alleviates PMS symptoms in OVX rats. Its therapeutic effects are associated with restored hormonal balance, reduced oxidative stress, improved lipid metabolism, and modulation of the ERα/MAPK/CREB signaling pathway in both uterine and hypothalamic tissues, suggesting an integrated neuroendocrine regulatory mechanism. Further studies employing functional inhibition experiments are warranted to confirm these causal relationships.